Growth kinetics of Staphylococcus aureus on Brie and Camembert cheeses. Issue 2 (14th April 2014) - Lee, Heeyoung; Kim, Kyungmi; Lee, Soomin; Han, Minkyung; Yoon, Yohan
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, we developed mathematical models to describe the growth kinetics of Staphylococcus aureus on natural cheeses. A five-strain mixture of Staph. aureus was inoculated onto 15 g of Brie and Camembert cheeses at 4 log CFU/g. The samples were then stored at 4, 10, 15, 25, and 30 °C for 2–60 d, with a different storage time being used for each temperature. Total bacterial and Staph. aureus cells were enumerated on tryptic soy agar and mannitol salt agar, respectively. The Baranyi model was fitted to the growth data of Staph. aureus to calculate kinetic parameters such as the maximum growth rate in log CFU units (rmax; log CFU/g/h) and the lag phase duration (λ; h). The effects of temperature on the square root of rmax and on the natural logarithm of λ were modelled in the second stage (secondary model). Independent experimental data (observed data) were compared with prediction and the respective root mean square error compared with the RMSE of the fit on the original data, as a measure of model performance. The total growth of bacteria was observed at 10, 15, 25, and 30 °C on both cheeses. The rmax values increased with storage temperature (P<0·05), but a significant effect of storage temperature on λ values was only observed between 4 and 15 °C (P<0·05). The square root model and linear equation were found to be appropriate for description of the effect of storage temperature on growth kinetics (R2=0·894–0·983). Our results indicate that the models developed in this study should be useful for describing the growth kinetics of Staph. aureus on Brie and Camembert cheeses.